Why Always Women?: Gender Inequality in Rusmini s Kenanga A Feminist Criticism Study - Riyanti, Apriani; Khasanah, Umul; Kamil, Indriyati; Dewi, Ni Putu Juliani Lestari; Lolowang, Imelda S. (Journal of English Culture, Language, Literature and Education, 2023)
The issue of gender equality is no longer a new one It arises along with the stereotype of men who have a higher nature than women In addition in terms of strength and rights women are also below men This aspect of gender inequality is one of the aspects developed by Rusmini in her novel Kenanga It tells the story of women who live under the pressure of men due to their gender This research was then made to examine every gender inequality behavior that occurs in this novel Using a qualitative method the research then applies a feminist approach in analyzing each event of gender inequality that occurs in Rusmini s novel Kenanga The results show that gender inequality against women mostly occurs due to stereotypes from the society in which they live This gender inequality occurs starting from the aspect that women s nature is under men therefore women must always obey men Moreover in terms of education women are also prohibited from getting a proper education than men because basically women s job is only to take care of men In addition women from the poor are often treated harshly because the customs enforced in society greatly differentiate between castes From this research a new direction is given that gender inequality needs to be a concern because considering today s developments it allows everyone including women to develop and have a career < p>